Utilização dos instrumentos econômicos fundiários para fomentar a regularização ambiental do empreendimento em área de REURB: estudo de caso do Distrito de Entre Rios, município de Nova Ubiratã/MT - NASCIMENTO, Suzete Veronica Amaral (2022)
Land regularization is a resource that prioritizes legalizing urban areas occupied irregularly, promoting improvements in the quality of life of the population and the urban environment. This study aims to investigate the use of economic instruments to promote the environmental regularization of the enterprise in areas of Reurb, in the District of Entre Rios. Regularization occurs through the tenure/property titration process as a new socioeconomic alternative for people and contributes to the adequacy of enterprises in accordance with current environmental legislation, as a way to mitigate environmental impacts, as well as ensure families the right to land tenure, establishing new paradigms of social inclusion. As a methodology, the deductive method and the techniques of bibliographic and documentary survey of qualitative characteristics are used. It is concluded that titration through urban land regularization - Reurb, fulfills the role of both the social and economic function, also fostering the economic development of the country